Designing a Partnership Model for Processing Potato Supply Chains with Farmers in West Java (Case Study: Supply Chain Division - PT PQR) - Supriatna, Yusup (Syntax Literate, 2026)
The increasing demand for processed potato products has created significant challenges for the domestic supply of industrial-grade potatoes in Indonesia. Despite the large production potential in West Java, the supply of processing potatoes remains limited due to low productivity, unsuitable potato varieties, fragmented supply chains, and weak partnership structures between farmers and processing industries. This study aims to design an effective partnership model to strengthen the processed potato supply chain between farmers and the processing industry, using a case study in the Supply Chain Division of PT PQR in West Java. The research adopts a qualitative case study approach supported by descriptive quantitative analysis. Primary data were collected through interviews, questionnaires, and field observations involving supply chain managers, partner farmers, cooperatives, and government representatives, while secondary data were obtained from company documents, government reports, and academic literature. Benchmarking, gap analysis, and risk assessment using the Risk Priority Index (RPI) were employed to evaluate existing partnership practices and identify critical risks. The results reveal significant gaps in institutional arrangements, production support systems, and risk management mechanisms within current partnerships. Key risks include seed quality issues, post-harvest handling problems, and coordination weaknesses among supply chain actors. To address these issues, this study proposes an enhanced aggregator-based partnership model supported by multi-year contracts, standardized agronomic practices, and formal governance mechanisms. In conclusion, strengthening institutional coordination, production support, and risk-sharing arrangements is essential to improve supply reliability and develop a sustainable processed potato supply chain in West Java.